Soil Incompressibility by 'Mixed' and Penalty Methods - Borja, Ronaldo I. (Philippine Engineering Journal; Vol 6 No 1 (1985), 2021)
In this paper two numerical methods of treating soil incompressibility are discussed, namely: (1) solution by ‘mixed’ formulation and (2) solution by penalty formulation. The numerical methods presented herein are finite element-based and assume that in the no-flow (undrained) condition, the deformation and pore pressure behavior of a saturated soil medium can be analyzed either by considering a two-phase soil-water relationship or by a single-phase continuum formulation.